Phosphorescent Platinum(II) Complexes with Mesoionic 1H‐1, 2, 3‐Triazolylidene Ligands. Issue 29 (13th June 2016) - Soellner, Johannes; Tenne, Mario; Wagenblast, Gerhard; Strassner, Thomas
Abstract: The synthesis and characterization of eight unprecedented phosphorescent C^C* cyclometalated mesoionic aryl‐1, 2, 3‐triazolylidene platinum(II) complexes with different β‐diketonate ligands are reported. All compounds proved to be strongly emissive at room temperature in poly(methyl methacrylate) films with an emitter concentration of 2 wt %. The observed photoluminescence properties were strongly dependent on the substitution on the aryl system and the β‐diketonate ligand. Compared to acetylacetonate, the β‐diketonates with aromatic substituents (mesityl and duryl) were found to significantly enhance the quantum yield while simultaneously reducing the emission lifetimes. Characterization was carried out by standard techniques, as well as solid‐state structure determination, which confirmed the binding mode of the carbene ligand. DFT calculations, carried out to predict the emission wavelength with maximum intensity, were in excellent agreement with the (later) obtained experimental data. Abstract : The synthesis and characterization of eight unprecedented phosphorescent C^C* cyclometalated mesoionic aryl‐1, 2, 3‐triazolylidene platinum(II) complexes with different β‐diketonate ligands are reported. All compounds proved to be strongly emissive at room temperature with the photoluminescence properties strongly dependent on the substitution of the aryl system and the β‐diketonate ligand. The bonding situation of the ligand mesoionic carbene (MIC) was confirmed by solid‐state structure determination (see figure).